2020
DOI: 10.1063/5.0022306
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical- and biocompatibility of oxygen and nitrogen plasma treatment using a PLA scaffold

Abstract: Plasma surface treatment has a wide range of applications in biomedicine. In the present study, flat polylactic acid (PLA) films were treated with oxygen and nitrogen, low-pressure, non-thermal plasma. The water contact angle of the PLA films dramatically decreased from 67° in the untreated surface to 34° and 38° in surfaces treated with nitrogen and oxygen plasma, respectively. Conversely, after the plasma treatment, the surface free energy of the films increased considerably from 45.73 mN/m to 66.51 mN/m. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Jordá-Vilaplana et al ( 2014) found a similar result for PLA with both O/C and N/C ratio increasing as a result of atmospheric plasma treatment. Slepička et al (2012) found that the O/C increased for poly-(4-methyl-1-pentene) (PMP) treated using an Ar plasma treatment from 0.003 for untreated to 0.401 following treatment at 8 W for 240 s. An increase in O/C and N/C ratio was also observed for oxygen and nitrogen, low pressure, non-thermal plasma treated PLA films (Davoodi et al, 2020).…”
Section: Resultsmentioning
confidence: 94%
“…Jordá-Vilaplana et al ( 2014) found a similar result for PLA with both O/C and N/C ratio increasing as a result of atmospheric plasma treatment. Slepička et al (2012) found that the O/C increased for poly-(4-methyl-1-pentene) (PMP) treated using an Ar plasma treatment from 0.003 for untreated to 0.401 following treatment at 8 W for 240 s. An increase in O/C and N/C ratio was also observed for oxygen and nitrogen, low pressure, non-thermal plasma treated PLA films (Davoodi et al, 2020).…”
Section: Resultsmentioning
confidence: 94%
“…This might explain why the PLA-2 polar groups get bigger. These newly formed bonds were characterized by activated functional groups, including carbonyl, carboxyl, and hydroxyl groups . It was possible to cut the long PLA-3 polymer chain by using an alkaline catalyst to break down PLA .…”
Section: Resultsmentioning
confidence: 99%
“…These newly formed bonds were characterized by activated functional groups, including carbonyl, carboxyl, and hydroxyl groups. 32 It was possible to cut the long PLA-3 polymer chain by using an alkaline catalyst to break down PLA. 33 Furthermore, treatment with DES induced a greater degree of bond cleavage (Figure 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The O1s spectrum of PLA untreated and treated samples can be decomposed into two peaks, attributed to the C−O and CO bonds. [ 34,35 ] The N1s spectrum of both samples could be decomposed into two, assigned to imine groups (CN) and amine groups (C−N). [ 36 ] However, the O 2 EDA treatment yielded a much higher concentration of amines when compared with PLA_NH 3 plasma‐treated samples, which corroborates the results obtained in the Orange II method and by fuchsin acid dye.…”
Section: Resultsmentioning
confidence: 99%